Plan de marketing para el complejo turístico “Somag” en el cantón la maná, año 2015 - Barcia Vera, Iris Katherine (2016)
This research was conducted at the resort Somag, Canton La Mana, in 2015, and was based in the environment in which it operates, its position in the market and how it influences the lack of a marketing plan in the same. Through research conducted determined that applying a marketing plan in the resort "Somag" will get a 10% over market positioning thus it would increase its profitability. Indian market research that Somag complex, has a very good position though is located in a strategic place, and it does not have adequate publicity and promotion to report its services and promotions. Therefore it was determined that the proposed strategies based on marketing mix are the most appropriate to inform the market on services and promotions. The strategies established for product, is a new brand where your logo is "the pleasure of enjoying" pricing strategy is to make a discount of 10% (tickets, lodging) for square strategy is to increase a new participant distribution channel. The strategy promoting an advertising campaign that will advertise ATL (Bonita radio channel Manavision, fences mana Central Park and one just outside the urban area on the road via Valencia) and BTL (sales promotions, sweepstakes will be used, discounts). The budget for the development of the marketing plan is $ 8,774.00 which is distributed in implementing each strategy, which will be financed by the owner. For proper development of advertising activities in chronological order to be constantly monitored in order to meet the objectives it will be. Keywords: Marketing. Marketing plan. strategies.